SNHG12 Promotes Autophagy by Blocking the mTOR-Primary Cilia-mTOR Loop via Activating the miR-181a-5p/miR-138-5p-INPP5E Axis in Chondrocyte - Weijia Feng; Lei Liu; Lin Sha; Zhenkai Wu; Jing Ding (International Journal of Clinical Practice)
Diseases related to cartilage abnormalities pose a serious threat to human health. Normal cartilage contains only one type of cell, chondrocytes. This study aims to investigate the impact of inositol polyphosphate-5-phosphatase E (INPP5E) on chondrocytes and its underlying mechanisms. Following transfection of small interfering RNA INPP5E into chondrocytes, real-time quantitative PCR (RT-PCR) and western blot (WB) assays were conducted to detect the expression of intraflagellar transport 88 (IFT88), Bcl-2-interacting protein 1 (Beclin1), microtubule-associated protein 1 light chain 3 alpha (MAP1LC3A), microtubule-associated protein 1 light chain 3 beta (MAP1LC3B), phosphoinositide 3-kinase (PI3K), protein kinase B (Akt), mammalian target of rapamycin (mTOR), collagen type II alpha 1 chain (COL2A1), and cyclin D1 (CCND1). Furthermore, immunofluorescence was used to detect the expression of acetylated α-tubulin and microtubule-associated protein 1 light chain 3 (LC3) II. RT-PCR, WB, and the dual luciferase assay demonstrated the regulation between SNHG12, hsa-miR-181a-5p, hsa-miR-138-5p, and INPP5E. Functional recovery experiments were used to observe the regulation of these factors on IFT88, Beclin1, LC3 I, LC3 II, p-PI3K, p-Akt, p-mTOR, collagen II, and cyclin D1 in chondrocytes. The results showed that silencing INPP5E inhibited the mRNA and protein expressions of the investigated factors in chondrocytes. SNHG12 promoted INPP5E expression by inhibiting hsa-miR-181a-5p or hsa-miR-138-5p, which resulted in regulation of the expression of various factors via the hsa-miR-181a-5p/hsa-miR-138-5p-INPP5E axis in chondrocytes. These findings provide a theoretical basis for the treatment of patients with cartilage-related abnormalities.